Method for reducing residual alkali content on the surface of sodium ion battery layered positive electrode material, sodium ion battery positive electrode material and sodium ion battery

Through the surface of sodium -fluoropphosphate on the surface of sodium ion battery layer -shaped positive material, the surface residual alkali content is reduced, the material processing performance is poor and the circulating performance deterioration is solved, and efficient electrochemical performance is achieved.

CN116495800BActive Publication Date: 2025-01-24コーネックス ニュー エナジー カンパニー リミテッド

Patent Information

Application Number
CN202310481328.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-01-24
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The residual alkali content on the surface of the layered positive electrode material of sodium ion battery is high, resulting in poor processing performance and deterioration of circulation performance.

Method used

By using sodium dysfluorophosphate to treat the surface of the sodium ion battery layer -like positive material, the surface residual alkali content is reduced. Specific steps include dispersing sodium diofluorophosphate in organic solvents, mixed with the positive electrode material to be treated to separate and washed, and finally obtained the positive electrode material after drying.

Benefits of technology

The processing of sodium ion battery layer -shaped positive materials has a high first discharge gram capacity and excellent circulatory performance, which improves the multiplier performance and high temperature storage performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116495800B_ABST
    Figure CN116495800B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a method for reducing the residual alkali content on the surface of a sodium ion battery layered positive electrode material, a sodium ion battery positive electrode material and a sodium ion battery. The method for reducing the residual alkali content on the surface of a sodium ion battery layered positive electrode material comprises the following steps: S1, dispersing sodium difluorophosphate in a first organic solvent to prepare a sodium difluorophosphate solution; S2, placing the sodium ion battery layered positive electrode material to be treated in a mixer, and then adding the sodium difluorophosphate solution to the mixer and mixing it with the sodium ion battery layered positive electrode material to be treated; S3, performing solid-liquid separation on the mixed solution to obtain a solid, then washing it, and finally drying it to obtain the treated sodium ion battery layered positive electrode material. The method provided by the present invention reduces the residual alkali content on the surface, so that the treated sodium ion battery layered positive electrode material has a higher first discharge gram capacity and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for reducing the residual alkali content on the surface of a layered positive electrode material for a sodium ion battery, a positive electrode material for a sodium ion battery, and a sodium ion battery. Background Art

[0002] In recent years, with the rapid development of the new energy industry, the lithium resources for the preparation of lithium-ion batteries are far from meeting the explosive growth demand. Sodium-ion batteries have attractive application prospects in the fields of energy storage, hybrid power, and replacement of lead-acid batteries due to their similar energy storage mechanism and abundant reserves as lithium-ion batteries.

[0003] At present, the main positive electrode materials for sodium ion batteries are Prussian blue, sodium vanadium phosphate, and layered oxides. Among them, the layered oxide material system has the advantages of high capacity and high compaction density and is regarded as the most promising positive electrode material. For example, CN114956202A discloses a sodium ion positive electrode material, which is an iron-manganese-nickel-based layered oxide material. In the preparation process of the layered oxide positive electrode material, in order to compensate for the volatilization of sodium during high-temperature calcination, the sodium content will be appropriately increased, so that a small amount of Na2O remains on the surface of the finally prepared layered oxide material, which will adsorb CO2 and H2O in the air to form residual alkali (NaOH and Na2CO3). The presence of this surface residual alkali will make the slurry easy to absorb water during the homogenization and coating process, causing the slurry to be jelly-like, and the processing performance will deteriorate. At the same time, the residual alkali on the surface of the layered oxide positive electrode material will decompose during the charge and discharge process and under high temperature conditions, and flatulence will occur, resulting in an increase in irreversible capacity loss during the battery charge and discharge process and deterioration of the cycle performance. Therefore, studying a method to reduce the residual alkali content on the surface is a technical problem that needs to be solved urgently in this technical field, and it is of great significance for the application of layered oxide positive electrode materials for sodium ion batteries in batteries. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for reducing the residual alkali content on the surface of a sodium ion battery layered positive electrode material, a sodium ion battery positive electrode material and a sodium ion battery. The present invention treats the surface of the sodium ion battery layered positive electrode material with sodium difluorophosphate, thereby reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, so that the treated sodium ion battery layered positive electrode material has a higher first discharge gram capacity and excellent cycle performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for reducing the residual alkali content on the surface of a layered positive electrode material for a sodium ion battery, the method comprising the following steps:

[0007] S1, dispersing sodium difluorophosphate (NaPO2F2) in a first organic solvent to prepare a sodium difluorophosphate solution;

[0008] S2, placing the sodium ion battery layered positive electrode material to be treated in a mixer, and then adding the sodium difluorophosphate solution into the mixer and mixing it with the sodium ion battery layered positive electrode material to be treated to obtain a mixed solution;

[0009] S3, performing solid-liquid separation on the mixed liquid to obtain a solid, then washing the solid with a second organic solvent, and finally drying to obtain a treated sodium ion battery layered positive electrode material.

[0010] The present invention uses sodium difluorophosphate to treat the surface of a sodium ion battery layered positive electrode material, thereby reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, so that the treated sodium ion battery layered positive electrode material has a higher initial discharge gram capacity and excellent cycle performance.

[0011] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the sodium difluorophosphate solution is added to the mixer in the form of a spray.

[0012] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the residual alkali includes at least one of NaOH and Na2CO3.

[0013] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the molar concentration of sodium difluorophosphate in the sodium difluorophosphate solution is 0.1 to 1.5 mol / L, for example, it can be 0.1 mol / L, 0.5 mol / L, 1 mol / L or 1.5 mol / L.

[0014] In the above method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, the chemical formula of the sodium ion battery layered positive electrode material is Na x1 MO y1 , wherein M includes one or more transition metal elements and alkaline earth metal elements, x1 and y1 satisfy charge balance, 0.5<x1<1.5, y1≥2, and the charge balance is satisfied between the elements in the chemical formula.

[0015] In the above method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, the chemical formula of the sodium ion battery layered positive electrode material is Na x2 Ni a Fe b Mn c Rn O2, wherein R represents a doping element, including at least one of Co, Cu, Mg, Zn, Sn, Zr, Ca, Al, V, Ti, Nb, W, Mo, Ce, Sr, Sb, and Y; 0.5<x2≤1, a>0, b>0, c>0, n≥0, a+b+c+n=1.

[0016] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the M includes at least one of Ni, Co, Mn, Cu, Fe, Mg, Zn, Sn, Zr, Ca, Al, V, Ti, Nb, W, Mo, Ce, Sr, Sb, and Y.

[0017] In the above method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, in step S2, the molar ratio of sodium difluorophosphate in the sodium difluorophosphate solution to the residual alkali on the surface of the sodium ion battery layered positive electrode material to be treated is 0.5:1 to 5:1, for example, the molar ratio can be 0.5:1, 1.0:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1 or 5.0:1, etc.

[0018] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the first organic solvent includes methanol, ethanol, ethylene glycol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, N-methylpropionamide, N-methylacetamide, N-methyl-2-pyrrolidone (NMP), acetonitrile, propionitrile, and acetone. One or more.

[0019] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, in step S2, the stirring speed of the mixer is controlled to be 100~500 rpm (for example, it can be 100 rpm, 300 rpm or 500 rpm, etc.), and the stirring time is 0.5~6 hours (for example, it can be 0.5 hours, 1.5 hours, 2.5 hours, 4.5 hours or 6 hours, etc.).

[0020] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, in step S2, the stirring temperature of the mixer is controlled to be 20~60°C, for example, it can be 20°C, 40°C, 50°C or 60°C.

[0021] In the above method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, the preparation method of the sodium ion battery layered positive electrode material to be treated comprises the following steps:

[0022] The sodium source and the sodium ion battery layered positive electrode material precursor are mixed evenly, sintered in a high-temperature oxygen atmosphere, cooled, crushed, and sieved to obtain the sodium ion battery layered positive electrode material to be treated.

[0023] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the sodium source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium hydroxide (NaOH), sodium acetate (CH2COONa), sodium phosphate (Na3PO5), sodium nitrate (NaNO3), and sodium sulfate (Na2SO4).

[0024] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the precursor of the layered positive electrode material of the sodium ion battery is selected from at least one of MCO3 and M(OH)2, wherein M includes at least one of a transition metal element and an alkaline earth metal element, for example, M includes at least one of Ni, Co, Mn, Cu, Fe, Mg, Zn, Sn, Zr, Ca, Al, V, Ti, Nb, W, Mo, Ce, Sr, Sb, and Y.

[0025] In the above method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, the sodium ion battery layered positive electrode material precursor is selected from Ni a Fe b Q 1-a-b (OH)2, or Ni a Fe b Q 1-a-b CO3, wherein Q is selected from at least one of Cu, Mn, Al, Mg, Zn, Sn, Ti, Zr, Sr, Sb, Nb, Mo, Y, Co, Ca, V, Ce, and W, 0≤a≤0.96, 0≤b<0.96, and 0≤1-ab≤0.96.

[0026] In the above method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, the particle size D50 of the sodium ion battery layered positive electrode material precursor is 2~18μm, for example, it can be 2μm, 6μm, 10μm, 14μm or 18μm, etc.

[0027] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the particle size D50 of the sodium source is 1~15μm, for example, it can be 1μm, 3μm, 5μm, 10μm or 15μm, etc.

[0028] In the above-mentioned method for reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, as a preferred embodiment, the molar ratio of the Na element in the sodium source to the M element in the sodium ion battery layered positive electrode material precursor is (1.01-1.10):1, that is, the molar ratio of Na / M is (1.01-1.10):1, for example, it can be 1.01:1, 1.04:1, 1.06:1 or 1.10:1, etc.

[0029] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the sintering temperature is 600-800°C, for example, the temperature is 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C or 800°C, etc.

[0030] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the heating rate of the sintering is 2 to 10°C / min, for example, the heating rate is 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min.

[0031] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the sintering time is 5 to 20 hours, for example, the time is 5.0h, 7.0h, 9.0h, 11.0h, 13.0h, 15.0h, 17.0h, and 20h.

[0032] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the mesh size of the sieve used for the screening is 200-500 mesh, for example, it can be 200 mesh, 300 mesh, 400 mesh or 500 mesh.

[0033] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the solid-liquid separation method is centrifugal separation using a centrifuge, and the centrifugal separation speed is 1000-8000rpm (for example, it can be 1000rpm, 3000rpm, 5000rpm or 8000rpm, etc.), and the centrifugal separation time is 0.1-1.0h (for example, it can be 0.1h, 0.3h, 0.5h, 0.7h or 1.0h, etc.).

[0034] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery, as a preferred embodiment, the second organic solvent includes methanol, ethanol, ethylene glycol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, N-methylpropionamide, N-methylacetamide, N-methyl-2-pyrrolidone (NMP), acetonitrile, propionitrile, and at least one of acetone.

[0035] In the above method for reducing the residual alkali content on the surface of the layered positive electrode material for sodium ion batteries, as a preferred embodiment, the number of washing in step S3 is 2 to 5 times.

[0036] In the above-mentioned method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, as a preferred embodiment, the drying method in step S3 is spray drying, and the spray drying includes feeding the washed organic solution containing the layered positive electrode material of the sodium ion battery into the spray drying equipment at a feed rate of 5 to 10 mL / min, wherein the inlet temperature of the spray drying equipment is 100 to 300°C (for example, it can be 100°C, 200°C or 300°C, etc.), the outlet temperature is 45 to 150°C (for example, it can be 45°C, 100°C or 150°C, etc.), and the atomization pressure is 0.1 to 0.5 MPa.

[0037] In a second aspect, the present invention provides a positive electrode material for a sodium ion battery, which is obtained by treating the positive electrode material for a sodium ion battery by the method for reducing the residual alkali content on the surface of a layered positive electrode material for a sodium ion battery as described in the first aspect.

[0038] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the second aspect.

[0039] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0040] (1) The present invention uses sodium difluorophosphate to treat the surface of the sodium ion battery layered positive electrode material, thereby reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, so that the treated sodium ion battery layered positive electrode material has a higher first discharge gram capacity and excellent cycle performance.

[0041] (2) The method provided by the present invention reduces the residual alkali content on the surface of the sodium ion battery layered positive electrode material, improves the processing performance of the sodium ion battery layered positive electrode material, and makes the treated sodium ion battery layered positive electrode material have excellent rate performance and high-temperature storage performance. At the same time, the process is simple, does not require a high-temperature secondary sintering process, and has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 A flow chart of the method for reducing the residual alkali content on the surface of layered positive electrode materials for sodium ion batteries provided by the present invention.

[0043] Figure 2 Cycle curves of batteries prepared with the positive electrode active materials provided in Example 3 of the present invention and Comparative Examples 1-2 under 1C / 1C conditions for 500 weeks.

[0044] Figure 3 This is a rate performance curve of a battery prepared with the positive electrode active materials provided in Example 3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0046] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0047] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0048] In the present invention, unless otherwise specified and / or described, all numerical values ​​involving the amount of components are "parts by weight" from beginning to end. The process parameters in the following examples that do not specify specific conditions are usually based on conventional conditions. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the amounts of the experimental reagents, unless otherwise specified, are all the amounts of reagents used in conventional experimental operations.

[0049] In a first aspect, the present invention provides a method for reducing the residual alkali content on the surface of a layered positive electrode material for a sodium ion battery. Figure 1 The method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery provided by the present invention is as follows: Figure 1 As shown, the method comprises the following steps:

[0050] S0, mixing the sodium source and the sodium ion battery layered positive electrode material precursor uniformly, sintering in a high temperature oxygen atmosphere, cooling, crushing, and screening to obtain the sodium ion battery layered positive electrode material to be treated, wherein the sodium source includes one or more of sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), sodium hydroxide (NaOH), sodium acetate (CH2COONa), sodium phosphate (Na3PO5), sodium nitrate (NaNO3), and sodium sulfate (Na2SO4); the sodium ion battery layered positive electrode material precursor is selected from Ni a Fe b Q 1-a-b (OH)2, or Ni a Fe b Q 1-a-b CO3, wherein Q is selected from at least one of Cu, Mn, Al, Mg, Zn, Sn, Ti, Zr, Sr, Sb, Nb, Mo, Y, Co, Ca, V, Ce, and W, 0≤a≤0.96, 0≤b<0.96, and 0≤1-ab≤0.96; the particle size D50 of the sodium ion battery layered positive electrode material precursor is 2~18μm; the particle size D50 of the sodium source is 1~15μm; the molar ratio of the Na element in the sodium source to the NiFeQ element in the sodium ion battery layered positive electrode material precursor is (1.01~1.10):1; the sintering temperature is 600~800℃, the sintering heating rate is 2~10℃ / min, the sintering time is 5~20 hours, and the mesh size of the sieve used for the screening is 200~500 mesh.

[0051] S1. Dispersing sodium difluorophosphate (NaPO2F2) in a first organic solvent to prepare a sodium difluorophosphate solution, wherein the molar concentration of sodium difluorophosphate in the sodium difluorophosphate solution is 0.1-1.5 mol / L, and the first organic solvent comprises one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, N-methylpropionamide, N-methylacetamide, N-methylpropionamide, N-methyl-2-pyrrolidone (NMP), acetonitrile, propionitrile, and acetone.

[0052] S2, placing the sodium ion battery layered cathode material to be treated in a mixer, and then adding the sodium difluorophosphate solution into the mixer in the form of a spray and mixing it with the sodium ion battery layered cathode material to be treated to obtain a mixed solution, wherein the chemical formula of the sodium ion battery layered cathode material is Na x2 Ni a Fe b Mn c R n O2, wherein R represents a doping element, including at least one of Co, Cu, Mg, Zn, Sn, Zr, Ca, Al, V, Ti, Nb, W, Mo, Ce, Sr, Sb, and Y; 0.5<x2≤1, a>0, b>0, c>0, n≥0, a+b+c+n=1; the molar ratio of sodium difluorophosphate in the sodium difluorophosphate solution to the residual alkali on the surface of the sodium ion battery layered positive electrode material to be treated is 0.5:1-5:1; the stirring speed of the mixer is controlled to be 100-500 rpm, the stirring time is 0.5-6 hours, and the stirring temperature is 20-60°C.

[0053] S3, the mixed liquid is subjected to solid-liquid separation to obtain a solid, and then the solid is washed with a second organic solvent, and finally dried to obtain the treated sodium ion battery layered positive electrode material, wherein the solid-liquid separation method is centrifugal separation using a centrifuge, the centrifugal separation speed is 1000-8000rpm, and the centrifugal separation time is 0.1-1.0h; the second organic solvent includes methanol, ethanol, ethylene glycol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propylene carbonate, ethylene carbonate, dimethyl carbonate, dicarbonate At least one of ethyl acetate, ethyl methyl carbonate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, N-methylpropionamide, N-methylacetamide, N-methylpropionamide, N-methyl-2-pyrrolidone (NMP), acetonitrile, propionitrile, and acetone; the washing times are 2 to 5 times; the drying method is spray drying, and the spray drying comprises feeding the washed organic solution containing the layered positive electrode material of the sodium ion battery into a spray drying device at a feed rate of 5 to 10 mL / min, wherein the spray drying device has an air inlet temperature of 100 to 300° C., an air outlet temperature of 45 to 150° C., and an atomization pressure of 0.1 to 0.5 MPa.

[0054] The existing mature water washing process will not only remove the residual alkali on the surface of the layered positive electrode material of the sodium ion battery, but also cause the sodium ions in its bulk phase to dissolve, destroying the structure of the layered positive electrode material of the sodium ion battery, resulting in a decrease in its first discharge capacity and poor cycle performance. Therefore, the water washing process is not suitable for the layered positive electrode material of the sodium ion battery.

[0055] The present invention uses sodium difluorophosphate to treat the surface of a sodium ion battery layered positive electrode material, thereby reducing the residual alkali content on the surface of the sodium ion battery layered positive electrode material, so that the treated sodium ion battery layered positive electrode material has a higher initial discharge gram capacity and excellent cycle performance.

[0056] In a second aspect, the present invention provides a positive electrode material for a sodium ion battery, which is obtained by treating the positive electrode material for a sodium ion battery by the method for reducing the residual alkali content on the surface of a layered positive electrode material for a sodium ion battery as described in the first aspect.

[0057] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the second aspect.

[0058] In order to further understand the present invention, the method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery, the positive electrode material of the sodium ion battery and the sodium ion battery provided by the present invention are described in detail in combination with the embodiments below. The protection scope of the present invention is not limited by the following embodiments.

[0059] In the following examples and comparative examples:

[0060] Test method for residual alkali content on the surface of layered positive electrode materials for sodium ion batteries: The NaOH and Na2CO3 contents (mass percentage) on the surface of layered positive electrode materials for sodium ion batteries are tested by potentiometric titration. First, 50g of the material is weighed and placed in 50mL of deionized water and mixed and stirred for 30min. After filtration, a clear liquid is obtained. 10mL of the clear liquid is titrated with a 0.05mol / L HCl standard solution to calculate the contents of NaOH and Na2CO3.

[0061] Example 1

[0062] The method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery provided in this embodiment comprises the following steps:

[0063] S01, firstly, the sodium ion battery layered positive electrode material precursor Ni 0.82 Fe 0.12 Mn 0.06 (OH)2 and sodium carbonate are sequentially put into a ball mill and mixed by ball milling at a speed of 600r / min for 6h, wherein the ball milling medium is zirconium oxide ball, the molar ratio of Na element in sodium carbonate to Ni, Fe and Mn elements in the sodium ion battery layered material precursor (the ratio of the molar number of Na element in sodium carbonate to the total molar number of Ni, Fe and Mn elements in the sodium ion battery layered material precursor) Na / (Ni+Fe+Mn) is 1.05, the particle size D50 of sodium carbonate is 5μm, and the particle size D50 of the sodium ion battery layered positive electrode material precursor is 8μm.

[0064] S02, the materials uniformly mixed in step S01 are heated to 790°C in a furnace with a high concentration of oxygen atmosphere (oxygen content ≥ 98.5%) at a heating rate of 3°C / min, sintered for 12 hours, and then naturally cooled to below 30°C, and then sieved through a 400-mesh standard sieve to obtain the sodium ion battery layered positive electrode material NaNi to be treated. 0.82 Fe 0.12 Mn 0.06 O2.

[0065] S1. Add soluble sodium salt NaPO2F2 into a glass beaker filled with ethyl methyl carbonate solvent at room temperature, and stir with a magnetic stirrer at 600 rpm for 40 minutes to obtain a uniformly mixed ethyl methyl carbonate solution of NaPO2F2, wherein the molar volume concentration of NaPO2F2 in the ethyl methyl carbonate solution is 0.5 mol / L.

[0066] S2. The sodium ion battery layered cathode material to be treated obtained in step S02 is placed in a high-speed mixer, and then stirred at a high speed. The stirring speed is controlled at 300 rpm and the stirring temperature is controlled at 25° C. Then, the ethyl methyl carbonate solution of sodium difluorophosphate prepared in step S1 is added to the liquid storage tank of the spray device, and the spray device is controlled to spray continuously so that the ethyl methyl carbonate solution of sodium difluorophosphate is added to the high-speed mixer in the form of a spray. The spraying time is controlled to be completed within 30 minutes. The molar ratio of the sprayed sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered cathode material to be treated is 0.8:1. After the spraying is completed, the high-speed mixer continues to stir for 2 hours to obtain a mixed solution.

[0067] S3, the mixed solution obtained in step S2 was centrifuged at a speed of 2000rpm for 15min, and then the precipitate after centrifugation was washed twice with ethyl methyl carbonate solvent, and the washed sodium ion battery layered positive electrode material was added to ethyl methyl carbonate to obtain a suspension with a solid content of 35%, and then the suspension was fed into a spray drying device at a feed rate of 6mL / min for spray drying, and the inlet temperature of the spray drying device was controlled to be 200°C, the outlet temperature was 65°C, and the atomization pressure was 0.3MPa. The dried material was sieved through a 325-mesh standard sieve to obtain the treated sodium ion battery layered positive electrode material.

[0068] Example 2

[0069] Compared with Example 1, the difference is that in step S2, the molar ratio of the sprayed sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered positive electrode material to be treated is 1.0:1, and the other process parameters and operation steps are exactly the same as those in Example 1, specifically comprising the following steps:

[0070] S01~S1: are exactly the same as steps S01~S1 in Example 1.

[0071] S2. The sodium ion battery layered cathode material to be treated obtained in step S02 is placed in a high-speed mixer, and then stirred at a high speed. The stirring speed is controlled at 300 rpm and the stirring temperature is controlled at 25° C. Then, the ethyl methyl carbonate solution of sodium difluorophosphate prepared in step S1 is added to the liquid storage tank of the spray device, and the spray device is controlled to spray continuously so that the ethyl methyl carbonate solution of sodium difluorophosphate is added to the high-speed mixer in the form of a spray. The spraying time is controlled to be completed within 30 minutes. The molar ratio of the sprayed sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered cathode material to be treated is 1.0:1. After the spraying is completed, the high-speed mixer continues to stir for 2 hours to obtain a mixed solution.

[0072] S3 is exactly the same as step S3 in Example 1.

[0073] Example 3

[0074] Compared with Example 1, the difference is that in step S2, the molar ratio of the sprayed sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered positive electrode material to be treated is 1.5:1, and the other process parameters and operation steps are exactly the same as those in Example 1, specifically comprising the following steps:

[0075] S01~S1: are exactly the same as steps S01~S1 in Example 1.

[0076] S2. The sodium ion battery layered cathode material to be treated obtained in step S02 is placed in a high-speed mixer, and then stirred at a high speed. The stirring speed is controlled at 300 rpm and the stirring temperature is controlled at 25° C. Then, the ethyl methyl carbonate solution of sodium difluorophosphate prepared in step S1 is added to the liquid storage tank of the spray device, and the spray device is controlled to spray continuously so that the ethyl methyl carbonate solution of sodium difluorophosphate is added to the high-speed mixer in the form of a spray. The spraying time is controlled to be completed within 30 minutes. The molar ratio of the sprayed sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered cathode material to be treated is 1.5:1. After the spraying is completed, the high-speed mixer continues to stir for 2 hours to obtain a mixed solution.

[0077] S3 is exactly the same as step S3 in Example 1.

[0078] Example 4

[0079] Compared with Example 3, the difference is that in step S1, the molar volume concentration of NaPO2F2 in the ethyl methyl carbonate solution of NaPO2F2 is 0.7 mol / L, and specifically comprises the following steps:

[0080] S01~S02: Exactly the same as steps S01~S02 in Example 3.

[0081] S1. Add soluble sodium salt NaPO2F2 into a glass beaker filled with ethyl methyl carbonate solvent at room temperature, and stir with a magnetic stirrer at 600 rpm for 40 minutes to obtain a uniformly mixed ethyl methyl carbonate solution of NaPO2F2, wherein the molar volume concentration of NaPO2F2 in the ethyl methyl carbonate solution is 0.7 mol / L.

[0082] S2~S3: Exactly the same as steps S2~S3 in Example 3.

[0083] Example 5

[0084] Compared with Example 3, the difference is that in step S2, the stirring temperature is controlled at 40° C. After the spraying is completed, the high-speed mixer continues to stir for 1.5 hours to obtain a mixed solution, which specifically includes the following steps:

[0085] S01~S1: are exactly the same as steps S01~S1 in Example 3.

[0086] S2. The sodium ion battery layered cathode material to be treated obtained in step S02 is placed in a high-speed mixer, and then stirred at a high speed. The stirring speed is controlled at 300 rpm and the stirring temperature is controlled at 40° C. Then, the ethyl methyl carbonate solution of sodium difluorophosphate prepared in step S1 is added to the liquid storage tank of the spray device, and the spray device is controlled to spray continuously so that the ethyl methyl carbonate solution of sodium difluorophosphate is added to the high-speed mixer in the form of a spray. The spraying time is controlled to be completed within 30 minutes. The molar ratio of the sprayed sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered cathode material to be treated is 1.5:1. After the spraying is completed, the high-speed mixer continues to stir for 1.5 hours to obtain a mixed solution.

[0087] S3 is exactly the same as step S3 in Example 3.

[0088] Comparative Example 1

[0089] Compared with Example 3, the difference is that only step S01 and step S02 are performed to obtain the sodium ion battery layered positive electrode material to be processed, and no subsequent operation or processing is performed.

[0090] Comparative Example 2

[0091] S1. The sodium ion battery layered positive electrode material to be treated obtained in step S02 of Example 3 is placed in a high-speed mixer, and then stirred at a high speed. The stirring speed is controlled at 300 rpm and the stirring temperature is controlled at 25°C. Then ethyl methyl carbonate is added to the liquid storage tank of the spray equipment, and the spray equipment is controlled to spray continuously so that ethyl methyl carbonate is added to the high-speed mixer in the form of spray. The spraying time is controlled to be completed within 30 minutes. The volume of the sprayed ethyl methyl carbonate is the same as the volume of the ethyl methyl carbonate solution of sodium difluorophosphate in step S2 of Example 3. The mass of the sodium ion battery layered positive electrode material to be treated is the same as the mass of the sodium ion battery layered positive electrode material to be treated in step S2 of Example 3. After the spraying is completed, the high-speed mixer continues to stir for 2 hours to obtain a mixed solution.

[0092] S2, the mixed solution obtained in step S1 was centrifuged at a speed of 2000 rpm for 15 min, and then the precipitate after centrifugation was washed twice with ethyl methyl carbonate solvent, and then the washed sodium ion battery layered positive electrode material was added to ethyl methyl carbonate to obtain a suspension with a solid content of 35%, and then the suspension was fed into a spray drying device at a feed rate of 6 mL / min for spray drying, and the inlet temperature of the spray drying device was controlled to be 200 ° C, the outlet temperature was 65 ° C, and the atomization pressure was 0.3 MPa. The dried material was sieved through a 325 mesh standard sieve to obtain the treated sodium ion battery layered positive electrode material.

[0093] Comparative Example 3

[0094] The method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery provided in this comparative example is basically the same as that in Example 3, except that the NaPO2F2 in step S1 is replaced by "sodium tetrafluoroborate", and specifically comprises the following steps:

[0095] S01~S02 are exactly the same as steps S01~S02 in Example 3.

[0096] S1. Add sodium tetrafluoroborate to a glass beaker containing ethyl methyl carbonate solvent at room temperature, and stir with a magnetic stirrer at 600 rpm for 40 min to obtain a uniformly mixed sodium tetrafluoroborate ethyl methyl carbonate solution, wherein the molar volume concentration of sodium tetrafluoroborate in the sodium tetrafluoroborate ethyl methyl carbonate solution is 0.5 mol / L.

[0097] S2. The sodium ion battery layered cathode material to be treated obtained in step S02 is placed in a high-speed mixer, and then stirred at a high speed. The stirring speed is controlled at 300 rpm and the stirring temperature is controlled at 25° C. Then, the ethyl methyl carbonate solution of sodium tetrafluoroborate prepared in step S1 is added to the liquid storage tank of the spray device, and the spray device is controlled to spray continuously so that the ethyl methyl carbonate solution of sodium tetrafluoroborate is added to the high-speed mixer in the form of a spray. The spraying time is controlled to be completed within 30 minutes. The molar ratio of the sprayed sodium tetrafluoroborate to the residual alkali on the surface of the sodium ion battery layered cathode material to be treated is 1.5:1. After the spraying is completed, the high-speed mixer continues to stir for 2 hours to obtain a mixed solution.

[0098] S3 is exactly the same as step S3 in Example 3.

[0099] Comparative Example 4

[0100] The method for reducing the residual alkali content on the surface of the layered positive electrode material of the sodium ion battery provided in this comparative example is basically the same as that in Example 3, except that step S2 is different from that in Example 3, and specifically comprises the following steps:

[0101] S01, firstly, the sodium ion battery layered positive electrode material precursor Ni 0.82 Fe 0.12 Mn 0.06 (OH)2 and sodium carbonate are put into a ball mill in turn and mixed by ball milling at a speed of 600r / min for 6 hours, wherein the ball milling medium is zirconium oxide ball, the molar ratio of Na element in sodium carbonate to Ni, Fe, and Mn elements in the sodium ion battery layered material precursor Na / (Ni+Fe+Mn) is 1.05, the particle size D50 of sodium carbonate is 5μm, and the particle size D50 of the sodium ion battery layered positive electrode material precursor is 8μm.

[0102] S02, the materials uniformly mixed in step S01 are heated to 790°C in a furnace with a high concentration of oxygen atmosphere (oxygen content ≥ 98.5%) at a heating rate of 3°C / min, sintered for 12 hours, and then naturally cooled to below 30°C, and then sieved through a 400-mesh standard sieve to obtain the sodium ion battery layered positive electrode material NaNi to be treated. 0.82 Fe 0.12 Mn 0.06 O2.

[0103] S1. Add soluble sodium salt NaPO2F2 into a glass beaker filled with ethyl methyl carbonate solvent at room temperature, and stir with a magnetic stirrer at 600 rpm for 40 minutes to obtain a uniformly mixed ethyl methyl carbonate solution of NaPO2F2, wherein the molar volume concentration of NaPO2F2 in the ethyl methyl carbonate solution is 0.5 mol / L.

[0104] S2. The sodium ion battery layered positive electrode material to be treated obtained in step S02 is placed in a high-speed mixer, and then the ethyl methyl carbonate solution of NaPO2F2 prepared in S1 is directly added to the high-speed mixer, and stirred at high speed to obtain a mixed solution. The stirring speed is controlled at 300 rpm, the stirring temperature is controlled at 25° C., the stirring time is 2.5 h, and the molar ratio of sodium difluorophosphate to the residual alkali on the surface of the sodium ion battery layered positive electrode material to be treated is 1.5:1.

[0105] S3, the mixed solution obtained in step S2 was centrifuged at a speed of 2000rpm for 15min, and then the precipitate after centrifugation was washed twice with ethyl methyl carbonate solvent, and the washed sodium ion battery layered positive electrode material was added to ethyl methyl carbonate to obtain a suspension with a solid content of 35%, and then the suspension was fed into a spray drying device at a feed rate of 6mL / min for spray drying, and the inlet temperature of the spray drying device was controlled to be 200°C, the outlet temperature was 65°C, and the atomization pressure was 0.3MPa. The dried material was sieved through a 325-mesh standard sieve to obtain the treated sodium ion battery layered positive electrode material.

[0106] Performance Test:

[0107] Preparation method of positive electrode sheet: The treated sodium ion battery layered positive electrode materials obtained in Example and Comparative Examples 2 to 4 and the to-be-treated sodium ion battery layered positive electrode material obtained in Comparative Example 1 are respectively used as positive electrode active materials, and the positive electrode active materials, acetylene black and PVDF are uniformly mixed in NMP at a mass ratio of 96.8:1.7:1.5 to prepare positive electrode slurry, and then the uniformly mixed slurry is coated on aluminum foil, vacuum dried at 120°C for 13 hours, and then rolled and die-cut to obtain a sodium battery positive electrode sheet.

[0108] Preparation method of negative electrode sheet: Hard carbon, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 96.5:0.9:1.5:1.1 to prepare a negative electrode slurry, and then the mixed slurry is coated on a copper foil, vacuum dried at 120°C for 13 hours, and then rolled and die-cut to obtain a sodium battery negative electrode sheet.

[0109] Assembly of sodium-ion battery: The positive and negative electrode sheets prepared above and a 9μm polypropylene separator (aluminum oxide is coated on one side as a ceramic layer) are prepared into a battery cell through a lamination process, and then the electrolyte is injected to assemble and prepare a 4.5Ah soft-pack battery. The electrolyte used is 1 mol / L NaPF6 / EC+EMC+DMC (volume ratio is 1:1:1) electrolyte. After the battery is filled, it is packaged and left to stand.

[0110] Sodium ion battery first discharge capacity in grams and cycle performance test: Sodium ion battery was first formed, the formation conditions are as follows: first charged at 0.02C constant current for 5h at 45℃, then charged at 0.05C constant current for 6h, then charged at 0.33C constant current and constant voltage to 4V at room temperature (cut-off current is 0.05C), after standing for 5min, discharged at 0.33C constant current to 2.0V, record the discharge capacity in grams at this time as the first discharge capacity in grams. Charge at 1C constant current and constant voltage to 4V (cut-off current is 0.05C) at 25℃, after standing for 5min, discharge at 1C constant current to 2.0V, record the discharge capacity in the first week and 500 cycles (500-week capacity retention rate = 500th week cycle discharge capacity / 1st week cycle discharge capacity), the test results are shown in Table 1 and Figure 2 shown.

[0111] Rate performance test: At 25°C, the sodium ion battery was charged and discharged at 0.2C / 0.2C current. After 5 cycles, the charge rate remained unchanged, and the discharge rate was adjusted. 5 cycles of charge and discharge were performed at 0.33C, 0.5C, 1C, 2C, and 0.33C respectively. The discharge gram capacity was obtained. The capacity retention rate of the Nth cycle = the discharge gram capacity of the Nth cycle / the first discharge gram capacity at 0.2C. The test results are as follows: Figure 3 shown.

[0112] Sodium ion battery 60℃, 30 days high temperature storage performance test: at room temperature, charge to 4V with a constant current of 0.33C, charge to 0.05C cutoff with a constant voltage, and let it stand for 1 hour. Use 0.33C current to discharge the battery to 2.0V and record the initial discharge capacity. After standing for 1 hour, charge to 4V with a constant current of 0.33C, charge to 0.05C cutoff with a constant voltage, and let it stand for 1 hour. Put the battery in a 60℃±1℃ high temperature box for storage for 30 days, take it out, put it at room temperature for 1 hour, and then discharge the battery to 2.0V with a constant current of 0.33C to test the residual capacity. The residual capacity divided by the initial discharge capacity is the capacity retention rate. The test results are shown in Table 1.

[0113] Table 1

[0114]

[0115] From Table 1, we can see at least the following points:

[0116] (1) It can be seen from Examples 1 to 3 and Comparative Example 1 that the present invention reduces the surface residual alkali content of the sodium ion battery layered positive electrode material by treating the surface of the sodium ion battery layered positive electrode material with sodium difluorophosphate, so that the treated sodium ion battery layered positive electrode material has a higher initial discharge gram capacity, excellent cycle performance and excellent high temperature storage performance. As the amount of sodium difluorophosphate increases, the residual alkali content gradually decreases. The applicant speculates that the reason may be that sodium difluorophosphate reacts chemically with the residual alkali, so that the surface residual alkali content decreases as the amount of sodium difluorophosphate increases.

[0117] (2) Comparative Examples 1 to 3 show that when treated with an organic solvent or an organic solvent containing sodium tetrafluoroborate, the residual alkali content on the surface cannot be significantly reduced.

[0118] (3) It can be seen from Example 3 and Comparative Example 4 that when an organic solvent containing sodium difluorophosphate is added in a spray form, the surface residual alkali content can be further reduced, thereby improving the initial discharge capacity, cycle performance and high-temperature storage performance of the layered positive electrode material for sodium ion batteries.

[0119] Figure 2 The cycle curve of the battery prepared with the positive electrode active material provided in Example 3 of the present invention and Comparative Examples 1-2 under the condition of 1C / 1C for 500 weeks is shown in FIG. Figure 2 It can be seen that the treated sodium ion battery layered positive electrode material provided by the present invention can significantly improve the cycle capacity retention rate of the sodium battery.

[0120] Figure 3 The rate performance curve of the battery prepared by the positive electrode active material provided in Example 3 of the present invention and Comparative Examples 1-2 is shown in FIG. Figure 3It can be seen that the treated sodium ion battery layered positive electrode material provided by the present invention can significantly improve the rate performance of the sodium battery. The applicant speculates that the reason may be that the residual alkali impedance on the surface of the sodium ion battery layered positive electrode material is relatively large, which affects the transmission and diffusion of sodium ions. The present invention reduces the surface residual alkali content, reduces the interfacial impedance of the positive electrode material, and thus improves the rate performance.

[0121] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for reducing the residual alkali content on the surface of a layered positive electrode material for a sodium ion battery, characterized in that: The method comprises the following steps: S1, dispersing sodium difluorophosphate in a first organic solvent to prepare a sodium difluorophosphate solution; S2, placing the sodium ion battery layered positive electrode material to be treated in a mixer, and then adding the sodium difluorophosphate solution into the mixer and mixing it with the sodium ion battery layered positive electrode material to be treated to obtain a mixed solution; S3, performing solid-liquid separation on the mixed liquid to obtain a solid, then washing the solid with a second organic solvent, and finally drying to obtain a treated sodium ion battery layered positive electrode material; The sodium difluorophosphate solution is added into the mixer in the form of a spray; The residual alkali is at least one of NaOH and Na2CO3; The method for preparing the layered positive electrode material for a sodium ion battery to be treated comprises the following steps: The sodium source and the sodium ion battery layered positive electrode material precursor are evenly mixed, sintered in a high-temperature oxygen atmosphere, cooled, crushed, and sieved to obtain the sodium ion battery layered positive electrode material to be treated.

2. The method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery according to claim 1, characterized in that: The molar concentration of sodium difluorophosphate in the sodium difluorophosphate solution is 0.1 to 1.5 mol / L; And / or, the chemical formula of the sodium ion battery layered positive electrode material is Na x1 MO y1 , wherein M includes one or more transition metal elements and alkaline earth metal elements, x1 and y1 satisfy charge balance, 0.5<x1<1.5, y1≥2, and the charge balance is satisfied between the elements in the chemical formula; And / or, in step S2, the molar ratio of sodium difluorophosphate in the sodium difluorophosphate solution to the residual alkali on the surface of the sodium ion battery layered positive electrode material to be treated is 0.5:1 to 5:1; And / or, the first organic solvent includes one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, N-methylpropionamide, N-methylacetamide, N-methyl-2-pyrrolidone, acetonitrile, propionitrile, and acetone.

3. The method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery according to claim 2, characterized in that: The M includes at least one of Ni, Co, Mn, Cu, Fe, Mg, Zn, Zr, Ca, V, Ti, Nb, W, Mo, Ce, Sr, and Y.

4. The method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery according to claim 1, characterized in that: In step S2, the stirring speed of the mixer is controlled to be 100-500 rpm, the stirring time is controlled to be 0.5-6 hours, and the stirring temperature is controlled to be 20-60°C.

5. The method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery according to claim 1, characterized in that: The sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, sodium phosphate, sodium nitrate, and sodium sulfate; And / or, the sodium ion battery layered cathode material precursor is selected from at least one of MCO3 and M(OH)2, wherein M includes at least one of a transition metal element and an alkaline earth metal element, and the molar ratio of the Na element in the sodium source to the M element in the sodium ion battery layered cathode material precursor is (1.01-1.10):1; And / or, the particle size D50 of the sodium ion battery layered cathode material precursor is 2-18 μm; And / or, the particle size D50 of the sodium source is 1-15 μm; And / or, the sintering temperature is 600-800°C, the sintering heating rate is 2-10°C / min, and the sintering time is 5-20 hours; And / or, the mesh size of the sieve used for the screening is 200-500 meshes.

6. The method for reducing the residual alkali content on the surface of the layered positive electrode material of a sodium ion battery according to claim 1, characterized in that: The solid-liquid separation method is centrifugal separation using a centrifuge, the centrifugal speed is 1000-8000rpm, and the centrifugal time is 0.1-1.0h; And / or, the second organic solvent comprises at least one of methanol, ethanol, ethylene glycol, n-propanol, isopropanol, n-butanol, isobutanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane, dimethylformamide, dimethylacetamide, N-methylpropionamide, N-methylacetamide, N-methyl-2-pyrrolidine, acetonitrile, propionitrile, and acetone; and / or, the number of washing in step S3 is 2 to 5 times; And / or, in step S3, the drying method is spray drying, and the spray drying includes feeding the washed organic solution containing the sodium ion battery layered positive electrode material into a spray drying equipment at a feeding rate of 5 to 10 mL / min, wherein the spray drying equipment has an air inlet temperature of 100 to 300° C., an air outlet temperature of 45 to 150° C., and an atomization pressure of 0.1 to 0.5 MPa.

Citation Information

Patent Citations

  • Precursor of sodium ion positive electrode material, preparation method and positive electrode material

    CN114956202A

  • Method for reducing pH value of sodium ion battery positive electrode material and application

    CN115498181A

  • Method for reducing residual alkali of positive electrode material and application

    CN116102083A

Cited By

  • Sodium-ion battery positive electrode material with stable circulation and preparation method of sodium-ion battery positive electrode material

    CN119674039A